Application of pre-contoured anatomic locking plate for treatment of humerus split type greater tuberosity fractures: A prospective review of 68 cases with an average follow-up of 2.5 years. Issue 6 (June 2018) - Hu, Chuanzhen; Zhou, Kaihua; Pan, Fugen; Zhai, Qilin; Wen, Weifeng; He, Xiaojian
Abstract: Objectives: Although various implants exist for 3- and 4-part proximal humerus fractures, few implants are appropriate for humerus split type greater tuberosity fractures. The goal of this study was to assess the efficacy of pre-contoured anatomic locking plate for humerus split type greater tuberosity fractures. Methods: A retrospective review of 68 patients with humerus split type greater tuberosity fractures treated with open reduction and internal fixation using anatomic locking plates between January 2014 and October 2016. Postoperatively, patient radiographs, functional results, and complications were reviewed. Results: All patients got a mean follow-up of 30.5 months (range 14–46 months). Average fracture healing time was 9.4 weeks (range, 8–14 weeks). Overall mean Constant score was 86.8% (range, 70%–96%). The result was rated as excellent in 25 patients (Constant score: 92.1%), good in 38 patients (Constant score: 85.3%) moderate in 5 patients (Constant score: 71.8%) and poor in 0 cases. The excellent-good rate was 92.6%. No recurrence of dislocation occurred in the 30 cases with shoulder dislocation. All fractures healed without the complications of wound infection, subacromial impingement syndrome, nonunion, secondary displacement, and implant loosening. Conclusion: Pre-contoured anatomic locking plate is a reliable option in treating humerus split type greater tuberosity fractures as it provides stable fixation with an early return to function. The surgical technique is easy and efficient.